(untitled) (Open Herald: Periodical of Methodical Research, 2026)
Antimicrobial resistance (AMR) has emerged as one of the most critical global health challenges of the 21st century, significantly undermining the efficacy of antibiotics and contributing to increased morbidity, mortality, and healthcare costs worldwide. The rapid emergence and dissemination of resistant bacterial strains are largely driven by the misuse and overuse of antimicrobial agents in human medicine, agriculture, and animal husbandry. This review provides a comprehensive analysis of the key mechanisms underlying antimicrobial resistance in pathogenic bacteria, including enzymatic drug inactivation, target site modification, overexpression of efflux pumps, and decreased membrane permeability. Furthermore, this study highlights the most clinically significant multidrugresistant (MDR) pathogens, with particular emphasis on both Gram-positive and Gram-negative bacteria that pose substantial therapeutic challenges. Recent global epidemiological trends are examined to illustrate the rising prevalence and widespread distribution of resistant infections. In addition, current diagnostic approaches—ranging from conventional phenotypic methods to advanced molecular techniques—are critically evaluated in terms of their accuracy, speed, and clinical applicability. The review also discusses existing and emerging strategies to combat AMR, including antimicrobial stewardship programs, the development of novel antibiotics, combination therapies, bacteriophage-based treatments, and alternative approaches such as antimicrobial peptides. Despite these advancements, significant challenges persist, particularly in drug discovery, regulatory frameworks, and the need for coordinated global action.